Evaluating the effects of hand weeding and selective herbicides on weeds control and maize (Zea mays L.) traits - Fakhari Rasoul; Moharramnejad Sajjad; Didehbaz Moghanlo Ghorban; Mammadova Ruhangiz (BIO Web of Conferences)
An experiment was performed with a randomized complete block design and four replications at the Agricultural and Natural Resources Research Center of Moghan during 2021-2022. The herbicides included Amaize-ing (terbuthylazine, 50% SC), Isoxaflutel + Tincarbazone (Adango 46.5% SC), Mesotrione + S-metolachlor + Lumax (Lumax 53.75% SE), U46 Combi Fluid (2. 4, D + MCPA 67.5% SL), Bromicide MA (Bromoxynil + MCPA 40% EC), Bromicide MA (Bromoxynil + MCPA 40% EC) + Cruze (Nicosulfuron 4% SC). The results of the analysis of variance showed a significant difference between treatments in terms of weeds density, weeds dry weight, maize grain yield, chlorophyll index (SPAD), leaf weight, proline, and catalase enzyme activity. The use of 1.8 and 2 L. ha-1 treatments of Amaize-ing, Adengo, Lumax, U46 Combi Fluid, Bromicid MA and Bromicid MA + Cruze herbicides had a favorable effect on weeds and resulted in a 20 to 30% increase in maize yield for these herbicides. The results showed that the highest chlorophyll content and leaf weight of maize was associated with treatments of Adengo, Lumax, U46 Combi Fluid, Bromicide MA and Bromicide MA + Cruze. But the Amaize-ing herbicide had a lower effect on leaf weight of maize. Also, increasing the dose of Amaize-ing increased the proline content and activity of catalase enzyme in maize.